Penerapan Metode Tutor Sebaya Untuk Meningkatkan Hasil Belajar Tari Siswa Di Kelas XI IPS 1 Di SMA Pertiwi 2 Padang - Yuni Rachtika Sari; Yuliasma Yuliasma; Zora Iriani (SENDRATASIK UNP, 2019)
This article aimed to explain and describe about the improvement of learning the dance art in students by using peer tutor method in class XI IPS 1 SMA Pertiwi 2 Padang. The type of this research was classroom action research which was conducted as much as 2 cycles. The subject was the students of grade XI IPS 1 SMA Pertiwi 2 Padang which amounted to 23 people. The data were collected by using observation sheets of the skills as well as documentation for the research. The results of this research showed that learning the art of dance using peer tutor method succeeded to improve the students’ learning outcomes at class XI IPS 1 SMA Pertiwi 2 Padang. This was evidenced on improving students’ activities and student learning outcomes on cycle I and cycle II which increased primely. On cycle I, the overall student positive activities were 38,64% and student negative activities were 16,89%. While, on cycle II student positive activites were 63,03% and student negative activities were  11,58%. The overall of students’ learning outcomes on cycle 1 was  55,21, meanwhile on cycle II, it has been risen to 80,21. Thus, the use of peer tutor method to enhance the outcomes in learning dance art in class XI IPS 1 SMA Pertiwi 2 Padang has already achieved very well.